2020
DOI: 10.1111/gcb.14953
|View full text |Cite
|
Sign up to set email alerts
|

Species interactions and climate change: How the disruption of species co‐occurrence will impact on an avian forest guild

Abstract: Interspecific interactions are crucial in determining species occurrence and community assembly. Understanding these interactions is thus essential for correctly predicting species' responses to climate change. We focussed on an avian forest guild of four hole‐nesting species with differing sensitivities to climate that show a range of well‐understood reciprocal interactions, including facilitation, competition and predation. We modelled the potential distributions of black woodpecker and boreal, tawny and Ura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 71 publications
(109 reference statements)
1
39
0
1
Order By: Relevance
“…This interpretation was also supported by the fact that start of egg-laying was delayed during 1970s-2010s although ambient temperatures increased and snow depth simultaneously did not increase prior to and during the egg-laying period. It is alarming that in similar adverse situation due to forest habitat loss and degradation in boreal zone are many forest-specialists belonging to different taxa [113][114][115][116][117][118][119][120][121] , and the situation may deteriorate as climate change progresses [2][3][4]122 , unless major measures to reverse this situation are taken and actually implemented as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation was also supported by the fact that start of egg-laying was delayed during 1970s-2010s although ambient temperatures increased and snow depth simultaneously did not increase prior to and during the egg-laying period. It is alarming that in similar adverse situation due to forest habitat loss and degradation in boreal zone are many forest-specialists belonging to different taxa [113][114][115][116][117][118][119][120][121] , and the situation may deteriorate as climate change progresses [2][3][4]122 , unless major measures to reverse this situation are taken and actually implemented as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Intraguild predation is a common feature of coexisting amphipod species (Dick et al, 1999;MacNeil et al, 2004); however, the influence of climate change on intraguild predation has received little focus to date (Brambilla et al, 2019). While some studies have found differential effects of water conductivity on the degree of intraguild predation between amphipod species (Dick & Platvoet, 1996;Kestrup et al, 2011) exchanges between freshwater and sea water, and thus withstand selection pressure at an early stage of the invasion process (Briski et al, 2018;Piscart et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Amphipod INNS are expected to continue to spread around the coastal areas of the Baltic Sea (Holopainen et al., 2016), and beyond (Grabowski et al., 2007; Son et al., 2020), with changing temperature and salinity conditions likely to further enhance ecological impacts. Intraguild predation is a common feature of coexisting amphipod species (Dick et al., 1999; MacNeil et al., 2004); however, the influence of climate change on intraguild predation has received little focus to date (Brambilla et al., 2019). While some studies have found differential effects of water conductivity on the degree of intraguild predation between amphipod species (Dick & Platvoet, 1996; Kestrup et al., 2011), there is a need to expand such studies to include other abiotic stressors associated with climate change, and to elucidate the associated effects of multiple predatory amphipod species on each other, as well as prey species.…”
Section: Discussionmentioning
confidence: 99%
“…This is clearly exemplified by acoustic surveys of singing birds. Noise and other disturbances determined by human activities may in fact reduce bird detectability by lowering observers' ability to hear a call or song ( Brambilla et al, 2020 ; Kissling et al, 2010 ; Pacifici et al, 2008 ). Therefore, the strong reduction of background noise caused by e.g.…”
Section: The Good: Effects Of Reduced Human Disturbance On Spatial Ormentioning
confidence: 99%